Analisis Spasial Kepadatan Penduduk dengan Penyebaran Demam Berdarah Dengue (DBD) di Wilayah Kota Banda Aceh - Zambruda Al Mabrura; Farrah Fahdhienie; Irma Hamisah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Dengue Hemorphic Fever (DHF) remains a significant public health challenge in Banda Aceh City, characterized by fluctuating annual case trends. Population density is heavily suspected of influencing transmission risk due to intense human interaction and vector presence. This ecological study aims to analyze the relationship between population density and DHF incidence, while identifying spatial distribution patterns and case clusters in Banda Aceh City from 2021 to 2025. Employing a quantitative descriptive-analytic design based on Geographic Information System (GIS), aggregate secondary data were analyzed using QGIS 3.34.11, SaTScan, GeoDa, and Google Earth software. The results revealed a total accumulation of 1,330 DHF cases, with the highest prevalence observed in males and the child-to-adolescent age groups. Statistical testing demonstrated no significant relationship between population density and DHF incidence (p-value > 0.05). However, spatial analysis confirmed the existence of dynamic annual case clustering, with several sub-districts identified as high-risk areas. In conclusion, although population density is not directly correlated, the distribution of DHF cases in Banda Aceh exhibits a distinct spatial clustering pattern. Consequently, DHF control efforts must be specifically targeted at high-risk cluster areas through a location-based intervention approach.